The use of hedges as politeness strategies in online complaints for services / Muna Liyana Mohamad Tarmizi - Mohamad Tarmizi, Muna Liyana (2015)
In the pragmatics context, hedges are significant politeness strategies and there was limited evidence on the use of hedges in complaints in the local context. Therefore, this study aimed to obtain empirical evidence on the use of hedges in 95 Malaysian naturally occurring online complaints for services. The objectives of this content analysis study were to examine a) 11 information components b) five (5) hedging strategies and c) nine (9) types of linguistic devices across the online complaints for services. Using relevant models and taxonomies of complaints, hedging strategies and linguistic devices, three (3) different criteria were developed to identify and categorize the information components, hedging strategies and types of linguistic devices found in the complaints. This content analysis had six (6) interesting findings. First, the 11 information components were found across the 95 naturally occurring online complaints for services in varying numbers ranging from one (1) to eight (8) information components. This indicated that none of the online complaints for services had all the 11 information components. Second, there were four (4) types of hedging strategies used as politeness strategies in 74 out of 95 online complaints for services. They were: a) HS2: To Mitigate, b) HS3: To Protect Oneself, c) HS4: To Elicit Sympathy and Consideration and d) HS5: To Appear Conciliatory with one (1) to two (2) types of hedging strategies in individual online complaints. Third, the four (4) hedging strategies reflected the use of eight (8) types of linguistic devices: LDl: Conditionals, LD2: Conjunctions, LD3: Personal Expressions, LD4: Modal Verbs, LD5: Adjectives, LD6: Adverbs and LD8: Pragmatic Idioms, LD9: Compound Hedges. Fourth, the hedging strategy HS2: To Mitigate was the dominant hedging strategy found across 70 complaints and nine (9) information components. Fifth, the four (4) hedging strategies were dominantly reflected in the information component IC3: Justification / Reasons for Complaints that was found in all of the 95 online complaints for services. Sixth, the linguistic device LD4: Modal Verbs was dominantly found across the four (4) hedging strategies. In view of the findings, there were two (2) important conclusions. First, the quality of online complaints for services written by Malaysian complainers varied in terms of the presence and absence of the information components, hedging strategies as politeness strategies and linguistic devices. This suggests a lack of knowledge among Malaysian complainers on the use of the required information components, hedging strategies and linguistic devices.Second, Malaysian complainers had the language ability to use four (4) hedging strategies as politeness strategies with a wide range of eight (8) types of linguistic devices. Based on the conclusions, three (3) recommendations are suggested. First, the criteria on the required information components, hedging strategies and linguistic devices used for this study should be taken seriously by educators for better instructions, as well as, for curriculum designers in developing academic syllabus and professional communication courses. Second, the authentic findings of this study should be acknowledged to book authors as an extension to the existing theories to cater the needs on lacking of sources on complaints writing. Third, the teaching of the content, politeness and language in complaints in terms of information components and hedging strategies as politeness strategies with relevant use of linguistic devices should be made explicit for ESL learners at secondary and tertiary levels, and, for professionals for effective communication of complaints.